Top Executive Locus of Control and Its Relationship to Strategy-Making, Structure, and Environment - Miller, Danny; Vries, Manfred F. R. Kets de; Toulouse, Jean‐Marie (Academy of Management Journal, 1982)
In a Canadian study the locus of control of top executives was found to bear a direct and significant relationship to the nature of corporate strategy but an indirect relationship to environment and to structure. More internal chief executives tended to pursue more product-market innovation, undertake greater risks, and lead rather than follow competitors.